보충적 보호대상자의 가족결합권 연구: 해외사례를 중심으로 - 김수경(Sookyung Kim); 김희주(HeeJoo Kim); 장주영(Juyoung Jang) (한국콘텐츠학회 논문지, 21(12), 2021)
As for international migration, family reunification is a key factor for the well-being and social integration of migrants. The UN ensures the right to family unity for the beneficiaries of complementary forms of protection. That includes those who are not recognized as refugees, but are nevertheless at risk of serious harm upon return to their country of origin, and thus are in need of international protection to the same degree as refugees. Although the Korean government provides humanitarian stay permits as complementary forms of protection, it does not guarantee family reunification as it does for refugees. This study aimed to examine the family reunification systems in Sweden, Ireland, Australia and Canada and to propose policy implications for family reunification of humanitarian status holders in Korea. The results showed that these countries commonly ensures the rights to family reunification although permission periods and scope vary by country. This study concludes that the Korean government should develop a legal system to ensure family reunification for humanitarian status holders since it is guaranteed as a basic human right by international covenants and promotes positive integration to countries of stay. 가족결합은 이주민의 행복과 사회통합에 중요한 요인이다. 따라서 유엔은 난민협약상 난민으로 인정되지는 않지만, 출신국으로 귀환할 경우 심각한 위해를 입을 상당한 근거가 있어 국제적 보호가 필요하다고 판단되는 보충적 보호대상자에 대해서도 난민과 같은 수준에서의 가족결합권 보장을 권고하고 있다. 한국은 보충적 보호 대상자와 유사한 인도적 체류자 제도가 있지만, 난민과 달리 가족결합권을 보장받지 못한다. 본 연구는 보충적 보호 대상자의 가족결합권과 관련하여 스웨덴, 아일랜드, 호주, 캐나다 등 해외사례를 살펴봄으로써 한국의 인도적 체류자 가족결합 보장에 대한 대안을 도출하고자 하였다. 분석결과 국가별로 허용기간이나 범위에 있어 차이가 있지만 공통적으로 가족결합을 인정하고 있었다. 또한 가족결합권은 국제규약에서 기본적 인권으로 간주할 뿐만 아니라 인도적 체류자처럼 취약한 상황에 있는 이들에게는 수용국에서의 적응을 위한 심리적 기반이라는 점에서 우리나라도 인도적 체류자의 가족결합권 보장을 구체화할 것을 제안하였다.